A comprehensive review of thermoelectric technology: materials, applications, modelling and performance improvement - Twaha, Ssennoga; Zhu, Jie; Yan, Yuying; Li, Bo (Elsevier, 2016)
Thermoelectric (TE) technology is regarded as alternative and environmentally friendly technology for harvesting and recovering heat which is directly converted into electrical energy using thermoelectric generators (TEG). Conversely, Peltier coolers and heaters are utilized to convert electrical energy into heat energy for cooling and heating purposes The main challenge lying behind the TE technology is the low efficiency of these devices mainly due to low figure of merit (ZT) of the materials used in making them as well as improper setting of the TE systems. The objective of this work is to carry out a comprehensive review of TE technology encompassing the materials, applications, modelling techniques and performance improvement. The paper has covered a wide range of topics related to TE technology subject area including the output power conditioning techniques. The review reveals some important critical aspects regarding TE device application and performance improvement. It is observed that the intensified research into TE technology has led to an outstanding increase in ZT, rendering the use TE devices in diversified application a reality. Not only does the TE material research and TE device geometrical adjustment contributed to TE device performance improvement, but also the use of advanced TE mathematical models which have facilitated appropriate segmentation TE modules using different materials and design of integrated TE devices. TE devices are observed to have booming applications in cooling, heating, electric power generation as well as hybrid applications. With the generation of electric energy using TEG, not only does the waste heat provide heat source but also other energy sources like solar, geothermal, biomass, infra-red radiation have gained increased utilization in TE based systems. However, the main challenge remains in striking the balance between the conflicting parameters; ZT and power factor, when designing and optimizing advanced TE materials. Hence more research is necessary to overcome this and other challenge so that the performance TE device can be improved further.